2007
DOI: 10.1242/jcs.03451
|View full text |Cite
|
Sign up to set email alerts
|

Increased phosphorylation and dimethylation of XY body histones in theHr6b-knockout mouse is associated with derepression of the X chromosome

Abstract: Mono-ubiquitylated H2A marks the transcriptionally silenced XY body during male meiotic prophase. Concomitant with H2AK119ub1, the ubiquitin-conjugating enzyme HR6B is also enriched on the XY body. We analyzed H2A and H2B ubiquitylation in Hr6b-knockout mouse spermatocytes, but no global changes were detected. Next, we analyzed phosphorylation of the threonine residues T120 and T119 that are adjacent to the K119 and K120 target sites for ubiquitylation in H2A and H2B, respectively. In wild-type cells, H2AT120p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
52
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 39 publications
8
52
0
Order By: Relevance
“…Hr6b knockout male mice are infertile, associated with dysregulation of chromatin structure in meiotic and post-meiotic cells. 63,66,67 In late pachytene nuclei of these cells, the SCs are longer, and the number of MLH1 foci is 20% increased in comparison to controls, 63 but crossover interference is not affected. 68 It might be suggested that Hr6b knockout spermatocytes contain more spontaneous DSB sites that contribute to the increased crossover rates.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Hr6b knockout male mice are infertile, associated with dysregulation of chromatin structure in meiotic and post-meiotic cells. 63,66,67 In late pachytene nuclei of these cells, the SCs are longer, and the number of MLH1 foci is 20% increased in comparison to controls, 63 but crossover interference is not affected. 68 It might be suggested that Hr6b knockout spermatocytes contain more spontaneous DSB sites that contribute to the increased crossover rates.…”
mentioning
confidence: 86%
“…21 In Hr6b knockout spermatocytes, the overall levels of H2B ubiquitylation and H3K4 trimethylation are not changed. 67 However, the regulation of several other histone modifications is disturbed, 67 indicating that changes in chromosome structure may be involved in mediating the enhanced recombination frequency in Hr6b knockout spermatocytes. Recent data have shown that in, C. elegans, a species in which pairing precedes recombination, chromatin condensing complexes regulate meiotic DSB distribution, directly implicating higher order chromosome structure in the regulation of meiotic DSB formation and repair.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…polymerase II, and are enriched for several repressive chromatin marks present on the sex body, including histone H3 dimethylated at lysine 9 (H3K9me2) and CBX1 (chromobox protein homolog 1, previously known as HP1) (Baarends et al, 2007;Greaves et al, 2006;Khalil et al, 2004;Namekawa et al, 2006;Turner et al, 2006). However, the X and Y chromosomes are continually remodelled during the transition between meiosis and spermiogenesis, and histone modifications associated with transcriptionally active chromatin [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…59 It remains unclear as to whether there is a requirement for HR6B-mediated ubiquitylation of H2B in this process, as Baarends et al detected H2Aub1, but not H2Bub1 during meiotic pachytene and in elongating spermatids. 60,61 An earlier study was able to detect H2Bub1 in elongating rat spermatids however, through the use of less stringent precipitation. 62 Downregulation of several autosomal genes was observed in the HR6B knockout, including many genes that regulate the cell cycle and embryonic development.…”
mentioning
confidence: 99%